Akulturasi Budaya pada Arsitektur Masjid Sunan Giri - Novita Siswayanti (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2016)
The Sunan Giri Mosque, one of the most remarkable mosques foun-ded by Sunan Giri, displays a most interesting combination of traditional Javanese and Hindu architecture. This paper uses research methods and descriptive analysis by describing the components of the mosque as analysis and interpretation. The Sunan Giri mosque displays the ‘Joglo forms’ typical of Javanese buildings, but surrounded by four pillars, and roofed in with overlapping ‘Meru’ just like in Hindu buildings, as is the Kalamkara archway and the pulpit of the mosque-shaped padmasana throne equipped with solar ornaments with Majapahit flourishes, the pineapple, arch-shaped mosque paduraksa reminiscent of the shape of the building on a grand kori kedathon in a Hindu Kingdom temple complex. Keywords : Sunan Giri Mosque, Acculturation Culture, Architecture Masjid Sunan Giri salah satu masjid walisanga yang didirikan oleh Sunan Giri yang arsitektur bangunannya vernacular berakulturasi dengan tradisional Jawa dan budaya yang bercorak Hindu. Artikel menggunakan metode penelitian analisis deskriptif dengan mendeskripsikan komponen-komponen bangunan masjid kemudian dilakukan analisis dan penafsiran. Akulturasi budaya yang tampak terlihat pada Masjid Sunan Giri ialah arsitektur bangunan Joglo tipikal bangunan Jawa yang disanggah dengan empat soko guru;Mustaka pada atap masjid bertumpang mirip meru pada bangunan Hindu, mihrab masjid yang berbentuk lengkungan kalamakara seperti candi, mimbar masjid berbentuk padmasana singgasana dilengkapi dengan ornamen surya Majapahit, florish dan nanas, gapura masjid ber¬bentuk paduraksa mengingatkan pada bentuk bangunan kori agung pada kedathon di komplek Kerajaan Hindu. Kata Kunci : Masjid Sunan Giri, Akulturasi Budaya, Arsitektur